The Implementation of Anagram Technique to Enhance the Seventh Grade Students Vocabulary Mastery - Siregar, Hema Malini Sari; Lumbanraja, Viator; Pangaribuan, Jontra Jusat (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2023)
This research was mainly conducted in order to prove that anagram technique could improve students’ vocabulary mastery of the seventh grade students of SMP Santo Thomas Medan in the Academic Year of 2021/2022 and to describe their responses towards the implementation of anagram technique during the processes of learning teaching. The quantitative data analysis showed the mean score increases from 78 in Pre-test with 65% of the students got score ≥ 75, to do the post test one with 74% of the students got score ≥ 75. From post test one 80 risen up to 92 in post test two with 97% of the students got score ≥ 75. Nearly all the students pass the minimum completion criterion which is 75. Their mean score is much higher than that. As for the qualitative data, they throwed their enthusiasm in learning with anagram technique because above 60% of students agree and 23% of students are strongly agree. The research findings showed that teaching vocabulary by using anagram technique to the seventh grade students of SMP Santo Thomas 3 Medan could improve their vocabulary mastery significantly.